Pengaruh Pemikiran Dan Penafsiran Ayat Pendidikan Oleh Buya Hamka Terhadap Perkembangan Pendidikan Islam Di Indonesia - Nuraini, Nabilah (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2024)
Buya Hamka, or Haji Abdul Malik Karim Amrullah, is a revolutionary figure in Islamic education in Indonesia. His progressive thoughts blend traditional Islamic values with modern ideas, creating a new educational paradigm relevant to contemporary developments. This study examines the influence of Buya Hamka's thoughts and interpretations of educational verses in the Quran on the development of Islamic education in Indonesia. Through "Tafsir Al-Azhar," Buya Hamka offers contextual interpretations that integrate traditional Islamic values with modern thought, establishing an educational paradigm pertinent to the times. This research employs qualitative analysis methods with book research for data collection. The findings reveal several implications of Hamka's interpretations for Islamic education in Indonesia, including implications for the nature of education, which is not merely focused on the transfer of knowledge, character education theory, and the ultimate goals of education. Additionally, the study identifies implications for Indonesian educational policies, methods of educational application that encompass both cognitive and psychomotor aspects, and the implications for educational institutions he founded.